Profile of antibiotic susceptibility test of bacterial pathogens isolated from the hands of university students in Nigeria - John Cletus Ihongbe; Salter Oluseun Aramide Adeyemo; Seyi Samson Enitan; Michael Olugbamila Dada; Oluchi Gladys Ofem; Effiong Effiong Joseph; Chinenye Alaezi Okorochi; Nwachi Idume Ogbonna (Trends in Infection and Global Health, 2022)
The aim of this study was to assess bacterial contaminants isolated from hands of undergraduate students of Babcock University, Nigeria. A total number of 200 students (100 males and 100 females) were randomly recruited and hand swabs were collected and inoculated on MacConkey and chocolate Agar. The biochemical tests were conducted to identify the bacterial isolates and antibiotic susceptibility testing was carried out using the disc diffusion method. Out of the 200 participants examined, bacterial contaminants were recovered from 154 (77.0%). The most frequently isolated organisms were Staphylococcus aureus (32.5%), followed by Escherichia coli (26.6%), coagulase negative Staphylococcus (20.8%) and then Klebsiella pneumoniae(20.1%). The antibiotic sensitivity showed that all coagulase negative Staphylococcus isolates were sensitive to ceftriaxone, levofloxacin, ciprofloxacin, imipenem, ofloxacin and azithromycin, but less sensitive to cefuroxime (50.0%) and amoxicillin (60.0%). S. aureus was sensitive to levofloxacin, ofloxacin, gentamycin and azithromycin while for Gram negative bacteria, E. coli was 100% sensitive to levofloxacin, imipenem, cefuroxime, ofloxacin, and ampiclox, but less sensitive to amoxicillin (20.0%). Klebsiella pneumoniae was sensitive to ceftriaxone and gentamycin, 100% and 90.0%, respectively, but less sensitive to amoxicillin (20.0%). In conclusion, some bacteria exist on the hands of undergraduate students of Babcock Students with varied antibiotic susceptibility patterns and therefore institutional implementation of hand hygiene practices should be implement among students in the university.